A fuzzy multi criteria decision making model for students' selection process based on technique for order performance by similarity to ideal solution (TOPSIS) / Daud Mohamad, Nor Hashimah Sulaiman and Fuziyah Ishak - Mohamad, Daud; Sulaiman, Nor Hashimah; Ishak, Fuziyah (2006)
In many instances, decision-making problems are ill defined as their objectives and constraints are not precisely known or available. The introduction of fuzzy set theory in decision-making has somehow given a path to more convincing results. Due to vagueness in the information obtained, fuzzy decision-making has played a vital role in dealing with this type of difficulty. One of the methods that see its vast usefulness is the fuzzy multi-criteria decision making (fuzzy MCDM). In this research, we focused on the technique for order performance by similarity to ideal solution (TOPSIS), one of the well known classical MCDM under fuzzy environment to give an alternative approach to selecting students for particular programs in Universiti Teknologi MARA (UiTM). The research considered three levels of students' selections namely diploma, degree and master levels. In this method, the decisionmakers would determine the weight for the criteria identified from the on-line application form and rate each applicant based on these criteria. The criteria are qualitative in nature and linguistic variable is most appropriate representation to use. The final output of the process using fuzzy TOPSIS would be the ranking of the students and the selection could be made based on this ranking. The results of the comparison made between rankings by the TOPSIS method and by the academic merit (CGPA) shows that there is a difference in the candidates' ranking. The proposed selection method by the TOPSIS seems to give a better and fair ranking for the candidates due to its rather comprehensive consideration of the evaluation criteria.